2021
DOI: 10.1038/s41467-021-27494-z
|View full text |Cite
|
Sign up to set email alerts
|

Tribo-electrochemistry induced artificial solid electrolyte interface by self-catalysis

Abstract: Potassium (K) metal is a promising alkali metal anode for its high abundance. However, dendrite on K anode is a serious problem which is even worse than Li. Artificial SEI (ASEI) is one of effective routes for suppressing dendrite. However, there are still some issues of the ASEI made by the traditional methods, e.g. weak adhesion, insufficient/uneven reaction, which deeply affects the ionic diffusion kinetics and the effect of inhibiting dendrites. Herein, through a unique self-catalysis tribo-electrochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Currently, a variety of approaches have been proposed to alleviate the problems of Na metal anodes such as optimizing the electrolyte with improved electrolyte additives, 14–18 introducing a protective layer, 19–22 constructing three-dimensional (3D) electrodes, 23,24 as well as alloy design to tune the Na metal surface chemistry. 10 However, these methods alone are insufficient to suppress volume expansion at current densities as high as 3.0 mA cm −2 and increase the interfacial impedance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a variety of approaches have been proposed to alleviate the problems of Na metal anodes such as optimizing the electrolyte with improved electrolyte additives, 14–18 introducing a protective layer, 19–22 constructing three-dimensional (3D) electrodes, 23,24 as well as alloy design to tune the Na metal surface chemistry. 10 However, these methods alone are insufficient to suppress volume expansion at current densities as high as 3.0 mA cm −2 and increase the interfacial impedance.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this attractive cycling performance is either comparable to or superior to most previously reported values for K anode stabilized by different strategies in various electrolytes (Figure 4g). [ 21,22,24,25,31,43,46–54 ]…”
Section: Resultsmentioning
confidence: 99%
“…Although lithium-ion batteries (LIBs) are ubiquitous in commercial applications ranging from low-powered wearables and medium-powered computing to megawatt-scale stationary storage, the abundance of lithium resources is limited in the construction of 3D host scaffolds, [21,22] application of solid-state electrolyte, [23] and artificial SEI/protective layers. [24,25] Among them, in situ and ex situ construction of SEI effectively pushed forward K anode engineering technique and alleviated certain aspects of the problems, while, the concept of reinforcing SEI falls short of the required electrode's ability that restrain the huge electrode volume change to prevent recurring dendriterelated issues during long-term cycling. As an alternative, developing 3D conductive scaffolds with K encapsulation is meritorious for dendrite-free composite K anode.…”
Section: Introductionmentioning
confidence: 99%
“…and 350 cycles (Li CP ) are characterized by SEM 51 . Figure 5D showed that the high-SDE substrate (Li CPA ) has a better impact on dendrite suppression than Li CP even Li CPA has long cycle.…”
Section: A New Dendrite Suppression Strategy -High Sde Substratementioning
confidence: 99%